2021
DOI: 10.1155/2021/1544067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Marginal and Internal Adaptation in Endocrowns Milled from Translucent Zirconia and Zirconium Lithium Silicate

Abstract: Purpose. This study aimed to compare marginal and internal adaptation in endocrowns made from translucent zirconia and zirconium lithium silicate using CAD-CAM technology. Materials and Methods. Twenty-eight freshly extracted upper molars were mounted in acrylic resin and underwent root canal therapy and endocrown preparation up to 2 mm above the cementoenamel junction. Endocrowns were CAD-CAM milled from zirconium lithium silicate (ZLS) and translucent zirconia (Zr). Internal and marginal adaptation was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…The results of the study showed that the marginal gap mean values ranged from 13.10 µm to 46.25 µm, which are below the clinically acceptable value of 120 µm as proposed by McLean and von Fraunhofer [ 21 ]. These results are consistent with previously reported values for endocrowns [ 8 , 9 ]. However, it should be noted that while the mean values in all study groups were below the acceptable limit, 10 out of 200 points in the 40 µm group had measurement values above 120 µm, indicating the importance of careful consideration of cement space parameters.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the study showed that the marginal gap mean values ranged from 13.10 µm to 46.25 µm, which are below the clinically acceptable value of 120 µm as proposed by McLean and von Fraunhofer [ 21 ]. These results are consistent with previously reported values for endocrowns [ 8 , 9 ]. However, it should be noted that while the mean values in all study groups were below the acceptable limit, 10 out of 200 points in the 40 µm group had measurement values above 120 µm, indicating the importance of careful consideration of cement space parameters.…”
Section: Discussionsupporting
confidence: 94%
“…Using SolidWorks, coronal tissues were cut 2 mm above the cementoenamel junction (CEJ) to simulate the extensive loss of coronal structures [ 5 , 28 , 29 ]. The occlusal margins were flat to represent butt joint preparation ( Figure 2 A) [ 5 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The occlusal margins were flat to represent butt joint preparation ( Figure 2 A) [ 5 , 29 ]. The pulp chamber was 3 mm in depth [ 30 ] with rounded angles and 10° internal wall divergence [ 4 , 28 , 29 ], ( Figure 2 B). A 0.1 mm thickness of the cement layer was also represented [ 10 , 31 ], as shown in Figure 2 B.…”
Section: Methodsmentioning
confidence: 99%
“…Since stereomicroscope does not integrate any sectioning or destruction of the restorations, it's less destructive and less time consuming than other measuring techniques mentioned previously, while possible errors from sectioning are avoided. (32) However, in this technique it is difficult to repeat the measurements from a corresponding angle and to differentiate the actual marginal gap from its projection. (31) Also, it's challenging to select the most significant points where the marginal opening should be measured and to identify the most apical part of the preparation margin.…”
Section: Discussionmentioning
confidence: 99%